Assets without a legal holder - Prostor, Jerneja (Lexonomica, 2016)
In recent years, the presence of certain assets, e.g. shares, immovable property or business shares, the owner or the holder of which no longer exists, can be identified in business practice. When the holder ceases to exist, he loses his legal personality and thus the ability to be the holder of rights and obligations in legal relationships. This article analyses legal regulation on the winding up of companies, in which the author sets out to answer the question of what leads to such unusual situations in practice. The winding up procedure should in fact resolve all legal relationships of those participating in a company. However, problems arise when cancelling a company from the court register without liquidation. Additionally, Slovenian Constitutional Court just recently found parts of the regulation of this procedure unconstitutional. The author offers a possible solution to the dilemma of how to transfer assets without a legal holder to a new holder or how to otherwise resolve the still existing legal relationships within the wound up company.
Keywords: delnice; izbris; podjetja; pravne osebe; premoženje; sodni register